SPEECH ACT FOUND IN SOEKARNO’S SPEECH ‘GANYANG MALAYSIA’ - BAHRI, SAIFUL (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords : speech act, locutionary acts, illocutionary acts, speech, Soekarno’s speech ‘Ganyang Malaysia.’ Language is an important factor in communication tools. By communication people can build a good relationship. In order to make a good communication, they have to understand well what the speaker says. In this case, learning speech act theory is important to cover this problems. Speech acts is an act which can be performed through utterance. In this study,  the writer examines the speech act theory in the speech ‘Ganyang Malaysia’ which is uttered by Soekarno. There are two research problems of the study, namely: (1) What locutionary and the type of illocutionary acts are produced in Soekarno’s speech ‘Ganyang Malaysia’ ?, (2) How are those acts syntactically realized in the speech ‘Ganyang Malaysia’ ?. This study was aimed to find out the locutionary, types of illoutionary act, and how those acts are realized in the speech ‘Ganyang Malaysia’.This study uses a qualitative approach. It is the descriptive study in textual analysis to analyze the components of speech acts covering the locutionary, illocutionary acts, and how those acts are realized in the speech ‘Ganyang Malaysia’ based on Levinson’s theory (1983), Yule’s theory (1996), and Langacker’s theory (1972) in the speech ‘Ganyang Malaysia’ which is uttered by Soekarno.This study reveals that two speech acts classification locutionary and types of illocutionary which are declarations, representatives, directives, expressives, commissives and types of sentence which are declarative and imperative are usedin the speech ‘Ganyang Malaysia.’ The illocutionary acts is frequently occured inspeech ‘Ganyang Malaysia’ is directive because the speaker tries to request thelisteners to do something. Moreover, illocutionary act frequently realized in thedeclarative because the speaker tries to inform something to the listeners throughthe speech.The writer suggests that the next researchers or writers observe perlocutionary act to make the deeper analysis in speech act and find another research object to be analyzed to show that speech act theory can be impelemented in many kinds of media. The writer also suggests the students of Study Program of English apply speech act in real life situation in order to understand well the context of the speaker’s utterances and they should be aware when they talk because every utterance has its own act which can affect the listeners.